IMPROVING STUDENTS’ MATHEMATICAL COMMUNICATION SKILLS ON DATA PROCESSING LEARNING MATERIALS THROUGH THE AIR (AUDITORY, INTELLECTUAL, REPETITION) LEARNING MODEL - Erlinda Indriani; I. Isrok'atun; Atep Sujana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Conveying ideas is needed to direct mathematical communication skills. In fact, mathematical communication abilities are indicated not to be maximized. Several conditions imply that the students' mathematical communication skills are less than optimal, one of which is teacher-based learning. In this paper, the research was conducted specifically to measure the improvement of students' abilities in mathematical communication by applying the AIR model to data processing learning material. The research was conducted using a quasi-experimental method with the Nonequivalent Control Group design. The results of the initial and final tests of students' mathematical communication skills indicate an improvement. The students at Grade V of SD Negeri Pataruman and SD Negeri Darmaraja I were the control and experimental classes for the research sample. Sampling was carried out using a purposive sampling technique. The results of the data analysis indicate that the students’ mathematical communication skill average score of the experimental class applying the AIR model was higher than the control class score by applying conventional learning. In the experimental class, the average score of mathematical communication skills was 43,34% in medium interpretation. Meanwhile, in the control class, the average score was 13,06% with a low interpretation. The description implies that the treatment in the experimental and control classes improves the students' mathematical communication skills differently.